The moderating effect of media exposure on the purchase intention of generic drugs: An application of the theory of planned behavior - Bautista, Reynaldo A. (Animo Repository, 2017)
Healthcare consumers in the Philippines seeking for quality and affordable medication stirred the demand for generic drugs; cheaper medicines that have the same level of efficacy as that of the popular-branded medications. Generic drug companies use various media platforms to further stimulate market growth. In line with this, the aim of this study is to predict the moderating effect of media exposure to the buying intention of generic drugs among consumers using Ajzen’s Theory of Planned Behavior (TPB). The TPB model is used to predict a person’s intention towards a behavior by examining three determinants – Attitude (ATT), Subjective Norm (SN), and Perceived Behavioral Control (PBC). The dependent variable of the study is the intention to buy generic drugs, while SN, AT and PBC are the explanatory variables. Moreover, media exposure was utilized as a moderating variable. The model was evaluated via Structural Equation Modeling (SEM) using SmartPLS 3. Although media exposure has no significant moderating effect to consumer’s decision in buying generic drugs, the explanatory variables (ATT, SN and PBC) established a significant relationship to buying intention.